GENEALOGI ULAMA HADIS NUSANTARA - Muhajirin Muhajirin (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2016)
This article tries to illustrate the geneology of hadith studies in Nusantara. Even though it does not cover such studies in the whole meaning, some basic points therein reveals important informations which are absent in previous studies. Al-Tarmisi, the important figure in the early history of hadith studies in Nusantara, enjoys a great reputation, particularly amongst the muhaddithîn. This is because, among some, he posed connected links (i.e. isnâd) to the transmitters of the first generation.